مدى تأثر الشركة بانسحاب الشريك (دراسة مقارنة) - شريفي, ويزة (جامعة مولود معمري, 2023)
تهدف دراسة موضوع انسحاب الشريك في القانون الجزائري والقانون المقارن إلى تحديد التنظيم القانوني لعملية انسحاب الشريك من الشركة، والوقوف على أسباب ومبررات عملية الانسحاب، وأهم الوسائل المتاحة لتحقيقه، خاصة وأنّ آثار الانسحاب تنصرف أساسا إلى الشريك المنسحب، كما تمتدإلى الشركة والشركاء والغير الذي تعامل مع الشركة. وقد أثبتت الدراسة المقارنة في القانونين الجزائري والفرنسي، مدى تأثر القانون الجزائري بالقانون الفرنسي، بسبب غياب تنظيم قانوني خاص في التشريع الجزائري لمسالة انسحاب الشريك من الشركة. ونتيجة لهذا الفراغ القانوني، استوجب الرجوع إلى القواعد العامة في القانون المدني، الذي ينظم عقد الشركة بصفة عامة، مع الأخذ بعين الاعتبار خصوصية الشركات التجارية والأحكام الخاصة المنظمة لها. إنّ انسحاب الشريك، قد يكون إراديًا في حالة قيامه بالتخلّي عن حقوقه الاجتماعية في الشركة، وقد يكون الانسحاب لا إراديا، عندما يكون عن طريق حكم قضائي، بحيث يتم في هذه الحالة إنهاء مهام الشريك من دون إرادته. وكقاعدة عامة، فإن انسحاب الشريك يِؤدي حتما إلى انقضاء الشركة، لاسيما إذا تعلق الأمر بشركات الأشخاص، إلا إذا كانت القوانين الأساسية للشركة والشركاء الباقون، قد قرروا خلاف ذلك، بمعنى استمرار الشركة. L’étude du retrait de l’associé en droit algérien et droit comparé a pour but de déterminer la réglementation juridique du mécanisme du retrait de l’associé de la société, afin de mettre l’accent sur les motifs du retrait, les moyens et techniques juridiques pour y parvenir, mais surtout ses effets, car le retrait touche principalement les droits de l’associé, les partenaires associés, et enfin les tiers. L’étude comparative du droit algérien et français, réaffirme l’influence du droit algérien par le droit français en raison de l’absence d’une règlementation spécifique relative au droit de retrait de l’associé. En raison de ce vide juridique, il est nécessaire de se référer aux règles générales du droit civil qui régissent le contrat de société, tout en tenant compte des spécificités des différents types de sociétés commerciales et des textes qui les régissent. Il est à préciser, que le retrait de l’associé peut être volontaire suite à sa renonciation à ses droits sociaux, mais il peut être involontaire dans le cas du retrait judicaire, quand il s’agit de mettre fin de manière unilatérale aux fonctions de l’associé. En règle générale, le retrait de l’associé entraine obligatoirement la dissolution de la société, notamment dans le cas des sociétés de personnes, sauf si les statuts de la société ou les associés ont convenus autrement, c’est à dire de la continuité de la société.
Keywords: Associés; Droit algérien; Droit comparé; Liquidation; Retrait d'associé; Scission; Société; التصفية; الشركاء; الشركة; القانون الجزائري; القانون المقارن; القسمة; انسحاب الشريك

أحكام التنازل عن الحصص وانتقالها في الشركة ذات المسؤولية المحدودة - بشيخ, ام الخير (Ibn Khaldun University of Tiaret, 2023)
المبدأ العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، إذ لا يجوز التنازل عن الحصص إلى الغير إلا بموافقة أغلبية الشركاء الحائزين لثلاثة أرباع رأس المال. وهو ما نصت علية المادة571 من القانون التجاري. والاستثناء حرية التنازل عن الحصص إلى الأصول والفروع والأزواج مالم ينص القانون الأساسي على تقييد التنازل. كما يخضع فيها التنازل عن الحصص للاسترداد وهو حق مقرر لمصلحة الشركاء والشركة لشراء الحصص المرغوب في التنازل عنها في حالة رفض الموافقة على المتنازل إليه. وإذا كان الأصل العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، فإن الحصص في هذه الشركة تنتقل بكل حرية إلى ورثة الشريك، بشرط أن لا يترتب على ذلك زيادة عدد الشركاء عن الحد الأقصى المقرر قانونا والذي هو 50 شريكا. ومع ذلك يمكن للشركاء تقييد انتقال الحصص إلى الورثة بشرط أن يتم إدراج هذا الشرط في القانون الأساسي للشركة. The general principle in a limited liability company is to restrict the assignment/ abdication of shares, as it is not permissible to assign shares to third parties except with the share-holders majority’s approval who possess three-quarters of the capital. This is what is stipulated in Article 571 of the Commercial Law. The exception is the freedom to assign/transfer shares to ascendants, descendants, and spouses, unless the Basic Law stipulates a restriction of abdication. In addition, the assignment of shares is subject to recovery, which is a right established in the interest of the partners and the company to purchase the desired shares to be assigned in the event of refusal to approve the assignee. Therefore if the general principle in the limited liability company is to restrict the abdication from shares, then the shares in this company are transferred freely to the partner’s heirs, provided that this does not result in an increase in the number of partners beyond the legally prescribed maximum, which are 50 partners. However, the partners can restrict the transfer of shares to the heirs, provided that this condition is included in the articles of association of the company.
Keywords: Associés; Cession d'actions; Droit de rachat; Offre d'actions; Société à responsabilité limitée

Preemption in Shares - Al-Rashidi, Hussein (UAEU Law Journal, 2023)
The Court of Appeals was presented with a dispute concerning the recovery of shares sold. The shareholder of a simplified joint-stock company had invoked the right of preemption, which is established by the Civil Code. The Court decided (on 1/10/2017, Appeals Nos. 1704, 1783/2017, Commercial, Civil, Governmental, Unpublished) that the shareholder could return the sold shares in accordance with his right of preemption. It considered that Company Law did not regulate the restitution of shares in the joint-stock company and that it was, therefore, necessary to refer to the provisions of the Civil Code. We think the decision of the Court of Appeals is subject to criticism. Firstly, even though the legislator does not regulate the restitution of the shares of the holding company, he refers to the regime applicable to the company from which the holding company takes its form. In this case, the holding company took the form of a joint-stock company, whose legislator had organized the shareholder's right to recover the shares offered for sale. Secondly, the Court did not follow the order of the official sources of the legal rule governing companies, namely company law, commercial law and commercial customs. Thirdly, the subject matter of the right of preemption is a real and undivided right, which is not the case for the share, since it is a personal right.

أساس المسؤولية الجزائية لجرائم الشركات التجارية - دحو, خديجة; دهلي, حبيبة (Ibn Khaldun University of Tiaret, 2023)
مسؤولية الشركات التجارية في الجانب الجنائي هي مفهوم قانوني يحدد امكانية مساءلة الشركات او المؤسسات التجارية جنائيا عن الجرائم التي ترتكب في اطار أنشطتها. تاريخيا كان يتم ملاحقة ومساءلة الأفراد جنائيا فقط عن افعالهم الاجرامية ومع طفرة قانون الأعمال وتزايد الوعي بضرورة مساءلة الشركات اصبحت مسؤولية الشركات التجارية جزائيا واقعا في العديد من البلدان. Corporate criminal liability is a legal concept that determines the possibility of holding corporations or commercial entities criminally accountable for crimes committed within the scope of their activities. Historically, only individuals were pursued and held criminally responsible for their criminal actions. However, with the evolution of business law and increased awareness of the need to hold corporations accountable, corporate criminal liability has become a reality in many countries Corporate criminal liability is based on the principle that a corporation can be considered an independent entity separate from its directors, employees, and shareholders. Therefore, if a criminal offense is committed within the company's operations, it can be prosecuted and tried independently of the individuals associated with it. The specific criminal offenses for which corporations can be held accountable vary according to national legislation, but they typically include acts such as fraud, bribery, money laundering, tax evasion, environmental violations, human rights abuses, forgery, unfair competition, and others. When a corporation is criminally prosecuted, it can face severe penalties, including hefty fines, asset seizure, dissolution of the
Keywords: Droit des sociétés commerciales; Personnes morales; Responsabilité pénale; الشخصية الاعتبارية; الشركات التجارية; المسؤولية الجنائية

حماية الغير في الشركات التجارية - محوز, العالية; سليمان, عائشة (Ibn Khaldun University of Tiaret, 2023)
تحتل حماية الغير المتعامل مع الشركات التجارية مكانة مهمة في القانون التجاري حيث كرس لها المشرع العديد من الأحكام والمبادئ القانونية التي تساهم في إستقرار المعاملات التجارية للشركات التجارية من جهة، والتي تدعم الثقة في معاملات الشركة مع محيطها الخارجي من جهة أخرى، وذلك نظرا للدور الذي يؤديه الغير في تطوير و إزدهار الشركة وتشجيع المتعاملين للإستثمار في هذا القطاع الاقتصادي المهم. قام المشرع بخطوات مهمة جعل من خلالها الغير يتدخل في حياة الشركة ونشاطها وذلك تخفيفا لآثار إعتبار هذا الغير عضوا خارجيا لا علم له بما يجري داخل الشركة التجارية، لكن تبني المشرع لأنظمة قانونية من أجل الغير لا يعني بلوغ النصوص القانونية هدفها الذي قررت من أجله . The protection of third parties dealing with commercial companies occupies an important place in the commercial law, as the legislator devoted many legal provisions and principles to it that contribute to the stability of commercial transactions of commercial companies on the one hand, and that support confidence in the company’s transactions with its external environment on the other hand, due to the role it plays Others contribute to the development and prosperity of the company and encourage customers to invest in this important economic sector. The legislator took important steps through which he made third parties interfere in the life and activity of the company in order to mitigate the effects of considering this third party as an external member who has no knowledge of what is going on inside the commercial company, but the legislator’s adoption of legal systems for the sake of third parties does not mean that the legal texts have reached their goal for which they were decided

تأسيس شركات المساهمة في التشريع الجزائري - يعقوبي, محمد (Ibn Khaldun University of Tiaret, 2023)
شركة المساهمة هي شركة أموال، لا يقل عدد شركائها عن سبعة شركاء يسمون بالمساهمين تتمثل حصصهم في الشركة بأسهم متساوية القيمة سهلة التداول لا يسأل هؤلاء عن ديون الشركة الا في حدود قيمة الأسهم التي اكتتبوا فيها، وكأي شركة وجب توفر الأركان الموضوعية العامة والخاصة والشكلية وإذا اختلف أحد هذه الأركان يعرضها للبطلان إما نسبي أو مطلق. وضع المشرع الجزائري طريقتين لتأسيس شركة المساهمة إما باللجوء العلني للادخار أو بدون اللجوء العلني للادخار أو بما يعرف بالتأسيس الفوري وتتميز المرحلتين بإجراءات معقدة، يقوم المؤسسون في كلتي المرحلتين بإعداد القانون الأساسي عن طريق جمعية عامة تأسيسية والمصادقة على الشروط المتفق عليها ووضع الشركة للجمهور قصد الاكتتاب فيها إذا ما لجأ المؤسسون لطريقة اللجوء العلني للادخار . أخيرا تسجيل الشركة في السجل التجاري كخطوة أخيرة من مراحل تأسيس الشركة. وأي مخالفة من شأنها تعطيل السير الحسن لتأسيس الشركة يعرضها للبطلان وتعدا المشرع البطلان إلا قيام مسؤولية مدنية وجزائية بتسليط عقوبات رادعة في حق المتخاذلين والمتعمدين في إفشال مشروع الشركة. A joint stock company is a company of funds, the number of its partners is not less than seven partners called shareholders whose shares in the company are represented by shares of equal value easy to trade, these are not responsible for the company's debts except within the limits of the value of the shares in which they subscribed, and like any company, we must provide the general, private and formal pillars, and if one of these pillars differs, it exposes it to invalidity, either relative or absolute. The Algerian legislator has developed two ways to establish a joint stock company, either by public resort to savings or without public resort to saving, or what is known as immediate incorporation, and the two stages are characterized by complex procedures, the founders in both stages prepare the basic law through a constituent general assembly, ratify the agreed terms and place the company for the public in order to subscribe to it if the founders resort to the method of public resort to savings, so that the company is finally registered in the commercial register as a final step of the company's establishment Any violation that may disrupt the proper functioning of the establishment of the com-pany exposes the company to invalidity and the legislator transgresses the nullity, except for civil and criminal liability to impose deterrent penalties against the negligent and deliberate in thwarting the company's project
Keywords: Création d'entreprise; Socitété par action; الإدخار; الإكتتاب